Preliminary mechanistic insights into the detection of ethanol vapour using MnO2 NRs-CNPs-poly-4-(vinylpyridine) based solid-state sensor operating at room temperature - Lesego Malepe; Derek Tantoh Ndinteh; Patrick Ndungu; Messai Adenew Mamo (Heliyon)
Semiconductor metal oxide gas sensors are widely used to detect ethanol vapours, commonly used in industrial productions, road safety detection, and solvent production; however, they operate at extremely high temperatures. In this work, we present manganese dioxide nanorods (MnO2 NRs) prepared via hydrothermal synthetic route, carbon soot (CNPs) prepared via pyrolysis of lighthouse candle, and poly-4-vinylpyridine (P4VP) composite for the detection of ethanol vapour at room temperature. MnO2, CNPs, P4VP, and MnO2 NRs-CNPs-P4VP composite were characterised using scanning electron microscopy, transmission electron microscopy, powder X-ray diffraction, Fourier transform infrared spectroscopy, and Raman spectroscopy. Five sensors were prepared, namely, sensor 1 (MnO2-NRs), sensor 2 (CNPs), sensor 3 (CNPs-P4VP composite of a mass ratio of 1:3), sensor 4 (MnO2 NRs-CNPs-P4VP composite of a mass ratio 1:1:3), and sensor 5 (MnO2 NRs-CNPs-P4VP composite of a mass ratio 2:1:3). All the five sensors were used detect to 2-propanol, acetone, ethanol, methanol, and mesitylene vapours at room temperature, but among all the tested sensors, sensor 4 was highly sensitive to ethanol vapour and less sensitive to 2-propanol, methanol, acetone, and mesitylene vapours. The response and recovery time of sensor 4 towards ethanol vapour at 20.4 ppm were 82 seconds and 74 seconds, respectively. The limit of detection on ethanol vapour using sensor 4 was 789 ppb. During detection, the ethanol vapour undergoes total deep oxidation on the surface of sensor 4.